Green Financing and SMES Performance in South Africa: Role of Environmental Management Accounting Practice - Adejayan, Adeola Oluwakemi; Doorasamy, Mishelle (International Journal of Energy Economics and Policy, 2025)
Most small businesses avoid the implementation of environmental accounting practices due to cost implications albeit may affect the impact of green initiatives on the financial performances of small businesses. Hence, this study investigates the moderating role of environmental management accounting practices (EMAP) on the relationship between green financing and financial performance of 10 manufacturing and export oriented small caps in South Africa from 2015 to 2024. ROA is employed as the proxy for financial performance while Green Capex and Environmental accounting disclosures are the predicting and intervening variables respectively. Using Driscoll and Kraay standard error panel regression, the results show that green finance has negative and significant effect on Return on Asset (ROA). Also, the moderating role of Environmental Management Accounting Practices strengthens the impact of green finance on ROA, though with non-significant effect. The study concludes that EMAP improves the financial performance of SMEs with green initiatives. More so, green initiatives alone are not sufficient to bolster financial performance of small businesses without incorporating environmental practices. Hence, its recommended that small businesses in South Africa should integrate the use of Environmental accounting practices in their operations that aligns with financial objectives by employing standardized EMAP tools that would assist them to monitor, quantify and assess environmental cost.